Efektifitas Penerapan Marketing Strategy dalam Upaya Meningkatkan Minat Belanja Konsumen di Swalayan Salafiyah Sukorejo Banyuputih Situbondo - Imroatus Sholiha; Lusi Oktaviani (Universitas 17 Agustus 1945, 2023)
The high interest of the Indonesian people in retail supermarkets makes competition for retail supermarkets increasingly high, so that appropriate and effective marketing strategies are needed. This research examines the effectiveness of marketing strategy implementation in an effort to increase consumer shopping interest at the Salafiyah Sukorejo Banyuputih Situbondo supermarket. This research is a field study using descriptive qualitative research methods, namely the reporting is described and conveyed in words. The data sources used use primary and secondary data, while the data collection techniques use observation, interviews and documentation. The validity of the data uses triangulation. The results of the research show that the marketing strategies carried out at Salafiyah supermarkets are very effective, although not all marketing strategy theories are implemented by Salafiyah supermarkets, but Salafiyah supermarkets' income increases from year to year due to implementing several marketing strategies that they implement in combination with several existing marketing strategy theories. Meanwhile, the obstacles faced in implementing marketing strategies include the lack of quantity of human resources and the lack of knowledge of human resources regarding retail supermarket marketing strategies.